2023
DOI: 10.14309/crj.0000000000000962
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Perivascular Epithelioid Cell Tumor Mimicking Hepatocellular Carcinoma

Abstract: Perivascular epithelioid cell tumors (PEComas) are rare mesenchymal neoplasms, and liver PEComas are extremely rare. They are usually discovered incidentally, and diagnostic pitfalls are frequent owing to similar imaging characteristics to other liver neoplasms. We present a patient whose evaluation was consistent with a right-sided hepatocellular carcinoma for which right hepatectomy was performed. Based on the final histopathological examination and immunohistochemistry, a diagnosis of PEComa was made. Immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
0
0
1
Order By: Relevance
“…Therefore, they may show intense contrast enhancement and close vessel relationship, especially in contrast phases. 19,20 In the study of Gao et al, "large blood vessel" was observed in approximately 80% of liver PEComas. 21 In our case, the mass was observed to be associated with the right portal vein branch (►Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, they may show intense contrast enhancement and close vessel relationship, especially in contrast phases. 19,20 In the study of Gao et al, "large blood vessel" was observed in approximately 80% of liver PEComas. 21 In our case, the mass was observed to be associated with the right portal vein branch (►Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The following are available online at , Table S1: Published cases of primary liver PEComas. References [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , ...…”
unclassified